Phase dependence of growth mechanisms in the daily energetics of the North Atlantic Oscillation - Kim, Minju; Sung, Mi-Kyung; Yoo, Changhyun (Royal Meteorological Society, 2024)
The North Atlantic Oscillation (NAO) is a dominant atmospheric variability in the Northern Hemisphere that has a substantial impact on weather and climate on various time scales. Here, we investigate the role of energy conversion terms day-by-day during the NAO life cycle. The relative timing and contribution of the energy conversion terms are quantified by projecting the terms onto the eddy total energy, eddy kinetic energy (EKE), and eddy available potential energy (EAPE) patterns associated with the NAO. The results show a remarkable phase dependence in the growth and maintenance mechanisms. For positive NAOs, the initial growth is driven by the barotropic interactions between the eddies propagating over North America. This suggests that a non-local growth mechanism plays an important role in the initiation of positive NAOs. In contrast, it is the baroclinic processes that initiate negative NAOs. The conversion of the mean APE into the EAPE and then into the EKE, processes which include eddy heat fluxes and vertical motions, results in the relatively local growth of negative NAOs. During the mature phase, the largest source of energy is the conversion of the mean APE into EAPE. Part of this is converted to EKE, making a substantial contribution to the maintenance of the EKE. This process is particularly important for negative NAOs. Here the daily energy cycles of the North Atlantic Oscillation (NAO) during the boreal winter are examined using budget analysis on the energy tendency equations. We find some phase-dependent process in the energetics of the NAO phases. The positive NAO events are driven by the barotropic process, whereas the negative NAO events are initiated by the baroclinic processes. Such a difference stems from the relative position of the NAO to the background state. image